Analysis of Stochastic Model of Market Sales Record - Bishop, Sheila A; Okagbue, Hilary I; Opanuga, Abiodun A (ExcelingTech, 2020)
Firms in Nigeria and other parts of the world are constantly faced with the problems of production of goods and services or cost of production visa vise customers’ satisfaction need, prices attached to these goods, services and profits. The challenge of trying to meet with the customers’ needs in terms of quality and quantity within best price practices (marginal profit) remains a vital part of decision making in all producing firms (manufacturing, service rendering companies, etc.). This research is born out of a concern for such challenges. The research addresses the issues of customer satisfaction needs based on four different brands of foam (mattresses) from a foam producing company in Lagos, Nigeria by analyzing the sales record of the different brands of foam using a simple transition probability matrix of a Markov chain. The analysis of a three - months sales record of the four brands of foams is studied using a stochastic model called Markov chain (M.C.). The sales record covered the three premier regions; North, West and East. The results of the analysis show that customer’s satisfaction need can be tied to so many factors: economy, quality of foam, family size, status and purpose of purchase. Analysis of the transition probabilities shows that brands B, which is a premium class product, is the most preferred brand by the customers, followed by brand C, which is a middle-class product. The foam producing company can use this analysis to slow down the production of brands A and D and increase the production of brands B and C. Instead of scraping out Brands A and D completely from production, the company should adopt new advertising strategies to promote brands A and D to improve on their sales.